Novel indenyl ligands bearing electron-withdrawing functional groups. (3rd November 2015) - Honzíčková, Iva; Vinklárek, Jaromír; Romão, Carlos C.; Růžičková, Zdeňka; Honzíček, Jan
Abstract : A new family of molybdenum complexes with an unprecedented substitution pattern in the indenyl ligand is reported. Abstract : A series of molybdenum complexes bearing new ligands is reported. The study covers a series of molybdenum compounds with the η 5 -coordinated indenyl ligand substituted with acyl-, ester- and amide-functions. This portfolio was extended by adding one representative with a η 3 -coordinated ester-substituted indenyl ligand. The functionalized indenes, necessary for the assembly, were prepared by convenient routes starting from inexpensive and readily available materials, enabling their production on a multigram scale. All structural types presented in this experimental study were supported by X-ray crystallographic data.